New accommodation models in city tourism: The case of Airbnb in Málaga - Fernández-Morales, Antonio; Mayorga-Toledano, María Cruz (My University, 2018)
Tourism is one of the fields where collaborative consumption has arrived with more intensity. Although the emergence of Airbnb in the city tourism market has helped increase the number of tourists in most of the cases, it also poses some problems, like the gentrification in central and historic areas, the rising of tourist pressure, or some regulation and legal issues. The main findings of this research reveal that Airbnb supply in the city of Málaga shows a very high rate of growth. The spatial pattern of the Airbnb supply is highly concentrated in the city centre. A similar pattern is exhibited by the hotel supply, with only slight differences. Measures of tourist pressure like the number of Airbnbn accommodations per inhabitant or the density of accommodations by ha are found to be similar to that in Barcelona.
Keywords: Turismo - Málaga; Economía colaborativa; City tourism; Airbnb; Málaga; Spatial pattern; Sharing economy